Señores generales, señores coroneles - Barron, Amalia (Producción IDHEC, 1976)
From the midst of the military coup of Colonel Hugo Bánzer Suarez and the overthrow of the populist government of General Juan José Torres, this documentary analyzes the history of Bolivian military interventions in the political life of the country, appealing to the testimonies of trade union leaders. and politicians. Gentlemen generals, gentlemen colonels takes its title from a poem by Nicolás Ortiz Pacheco written during the Chaco War. Juan Lechín is interviewed about the popular resistance struggle of 1971, while former government minister Jorge Selum, a survivor of the massacre at the University of Santa Cruz, refers to the repression. Former CIA agent Philip Agee, author of the CIA Journal, offers his testimony on the intervention of US intelligence agencies, while Regis Debray talks about his own experience in Bolivia during the Guerrilla del Ché. --